Group Counseling Services To Improve Self-Concept Through Good Adjustment In The New Normal Era - Zarisman, Esi; Firman, Firman; Netrawati, Netrawati (Widyagogik, 2023)
Children who have a good self-concept will see themselves well too, and this will affect their adjustment. The purpose of this study is to find out 1. An overview of a person's self-concept 2. The way a person adapts. Good adjustment will help someone to be able to interact with their environment, especially the school environment. The results of the discussion show that a good self-concept or a person's perspective on himself is good, then he will easily accept all the weaknesses and strengths in himself and this can help him to be able to adjust himself well.